The Effectiveness of Monitoring Book for Teacher-Parent Collaboration - Indria, Anita; Hendrisab, Hendrisab; Hanizon, Wirman; Hanton, Hanton (Ahlussunnah: Journal of Islamic Education, 2025)
This research aimed at describing and solving problems related to the use of monitoring book that did not work optimally. Monitoring book as a medium of communication between teachers and parents should be used as best as possible so that even when parents are busy with their work, they can still control their child’s development at home. After conducting research, problems were found in the field that the use of monitoring book was still not effective because there were several problems that needed to be solved. Through qualitative research methods with a descriptive analytical approach, it was found that problems with the use of monitoring book were caused by a lack of attention, concern, and participation of parents in supervising children studying at home. It was because parents did not sign the monitoring book as proof that parental control over their child’s learning at home did work. This research found that the reason for this was that the rules set at the beginning of the year were not implemented as they should have been.